Leucine rich repeat kinase 2 (LRRK2) peptide modulators: Recent advances and future directions. Issue 1 (11th December 2021) - Helton, Leah G.; Rideout, Hardy J.; Herberg, Friedrich W.; Kennedy, Eileen J.
Abstract: Leucine rich repeat kinase 2 (LRRK2) is the most common genetic contributor to Parkinson's disease (PD), a complex neurodegenerative disorder affecting nearly 10 million people worldwide. Pathogenic mutations within LRRK2 often induce increased kinase activity, an effect that can be abolished with many small molecule inhibitors; however, these small molecule inhibitors are currently limited by their toxicities. Given the large and complex nature of LRRK2, more recent efforts have focused on protein–protein interactions (PPIs) involving LRRK2 and how they can contribute to PD. Here, we review recently resolved structures of LRRK2 and highlight unique interfaces driving both catalytic and non‐catalytic activities. Combining new structural information with established in vitro and in vivo data clarifies the role of PPIs in driving LRRK2‐mediated disease pathogenesis. Since constrained peptides and peptidomimetics have the potential to engage with elongated, hydrophobic interfaces that were previously considered "undruggable, " they may provide a unique handle for LRRK2 targeting. Here, we discuss the use of constrained peptides and peptidomimetics to target LRRK2 as a strategy to downregulate its pathological activity. Abstract :